Pembuatan Aplikasi Penawaran Perangkat Dengar Musik untuk Komunitas Audio Kere Hore Berbasis Android - Leonardo Halasantua; Henri Septanto (UNIVERSITAS KALBIS, 2022)
The purpose of this research is to create an application for offering online music listening devices in the Kere Hore Audio Community based on Android. The online music listening device offering application provides freedom to members in the Kere Hore Community to offer music listening devices through a mobile application using an android smartphone. Bidding can be made by entering the bid nominal for the items available in the offer. The tools will be available from members who have published the item to be offered. The software development method used in this research is RUP using UML modeling. This application is designed using Android Studio software with the Java programming language, PHP, Laravel Framework, and database structures using MySQL. The result of this application is an application offering an Android-based musical instrument hearing device.